La alternativa ecosocialista. Una entrevista con Michael Löwy (2020)
The planetary ecological crisis deepens at an accelerated rate endangering the balance of life and the survival of human civilization. In the last half century, several radical alternatives of eco-social transformation have emerged in the field of political ecology to challenge the dominant system from different ethical, ecological, social, and economic grounds. One of them, ecosocialism, arose in the 1970s in Europe and has been growing in the last 20 years in Latin America. Although it has variations, Marxism constitutes the main theoretical-methodological core of ecosocialism. Michael Löwy is a French-Brazilian ecosocialist philosopher and sociologist. He is also one of the most important figures of Marxist thinking: a political-philosophical node for the debate between Europe and Latin America. Here we present an April 2020 interview with professor Löwy and the transcription of two ecosocialist manifestos, The First International Ecosocialist Manifesto of 2001 and The Belem Ecosocialist Manifesto of 2009, both coauthored by the interviewee.